2009
DOI: 10.1902/jop.2009.090250
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease Is Associated With Gestational Diabetes Mellitus: A Case‐Control Study

Abstract: Background Few studies have specifically examined the relationship between periodontal disease and gestational diabetes mellitus (GDM). The objective of this study was to examine whether maternal periodontal disease is associated with GDM. Methods A case-control study was conducted of 53 pregnant women with GDM and 106 pregnant women without GDM at Woman’s Hospital, Baton Rouge, USA. The periodontal examinations were performed by a calibrated dentist who was blinded on the diabetic status of the pregnant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
1
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(125 citation statements)
references
References 42 publications
6
108
1
10
Order By: Relevance
“…Recent studies have shown an association between periodontitis during pregnancy and low birth weight (LBW), very low birth weight (VLBW), preeclampsia, and GDM (Corbella et al, 2016;Guimarã es et al, 2012;Ha, Jun, Ko, Paik, & Bae, 2014;Xiong et al, 2009). Guimarã es et al (2012 showed in their crosssectional study of 1,206 postpartum women that "maternal periodontitis was associated with a decrease in mean birth weight, as well as LBW and VLBW" (p. 1024).…”
Section: Periodontitismentioning
confidence: 99%
“…Recent studies have shown an association between periodontitis during pregnancy and low birth weight (LBW), very low birth weight (VLBW), preeclampsia, and GDM (Corbella et al, 2016;Guimarã es et al, 2012;Ha, Jun, Ko, Paik, & Bae, 2014;Xiong et al, 2009). Guimarã es et al (2012 showed in their crosssectional study of 1,206 postpartum women that "maternal periodontitis was associated with a decrease in mean birth weight, as well as LBW and VLBW" (p. 1024).…”
Section: Periodontitismentioning
confidence: 99%
“…При этом ПД рассматривается как независимый ФР для неблагоприятного исхода беременности, на который мож-но оказывать влияние [15,34]. Кроме того, установлена ас-социация между гестационным СД и ПП [35].…”
unclassified
“…It increases the risk of polyhydramnion, hypertension, recurrent urogenital infections, Caesarean delivery, birth injury and the persistence of diabetes after pregnancy or its return during a subsequent pregnancy 13 . Gestational diabetes has been associated with periodontal disease in a cross-sectional study 13 and a case-control study 14 . The most common periodontal disease in pregnancy is gingivitis 15 .…”
Section: Discussionmentioning
confidence: 99%